Determinants of Local Governments attitude towards Local Agenda 21: an empirical analysis - Jose M Barrutia; Carmen Echebarria; Itziar Aguado (European Regional Science Association (ERSA), 2010)
Previous research has identified factors affecting Local governments' (LGs) attitude to Local Agenda 21 (LA21) (Echebarria, et al. 2009). This research is addressed to propose a measurement model and contrast it in the case of a specific region, the Basque Country. Research results support that LGs attitude to LA21 (in terms of value, satisfaction and loyalty) is explained by internal characteristics of the LGs (such as the existence of key individuals and the LG' propensity towards citizen participation) and factors related to the environment of the LGs which is fostered, fundamentally, by the higher levels of government (HLGs) which can create connected or networking processes. Measurement model could be used in other contexts in order to accept or refuse the results of this research and offer politicians a guide to achieve a more generalised diffusion of LA21 processes.
Keywords: 330; Local Agenda 21; attitude; networking; attitude determinants